2014
DOI: 10.7554/elife.02634
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial actin MreB forms antiparallel double filaments

Abstract: Filaments of all actin-like proteins known to date are assembled from pairs of protofilaments that are arranged in a parallel fashion, generating polarity. In this study, we show that the prokaryotic actin homologue MreB forms pairs of protofilaments that adopt an antiparallel arrangement in vitro and in vivo. We provide an atomic view of antiparallel protofilaments of Caulobacter MreB as apparent from crystal structures. We show that a protofilament doublet is essential for MreB's function in cell shape maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
322
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(360 citation statements)
references
References 93 publications
(152 reference statements)
35
322
2
1
Order By: Relevance
“…As the concentration of A22 is increased, MreB becomes localized to the membrane and more fluorescence is found in the cytoplasm. These results are consistent with previous work showing that MreB bound to A22 weakens interprotofilament contacts, thus decreasing the stability of MreB polymers (27,28).…”
Section: Mreb Polymers In A22-treated Cells and The Effect Of A22 On supporting
confidence: 93%
See 3 more Smart Citations
“…As the concentration of A22 is increased, MreB becomes localized to the membrane and more fluorescence is found in the cytoplasm. These results are consistent with previous work showing that MreB bound to A22 weakens interprotofilament contacts, thus decreasing the stability of MreB polymers (27,28).…”
Section: Mreb Polymers In A22-treated Cells and The Effect Of A22 On supporting
confidence: 93%
“…In cells treated with A22, the drug interacts with nucleotide-bound MreB to prevent nucleotide hydrolysis and destabilize filaments (28,32). A22 treatment and mutations perturbing the nucleotide-binding pocket of MreB have the potential to alter the geometry of the polymer as it has been shown that the angle between adjacent MreB monomers depends on the state of the bound nucleotide (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S4A), which we suggest represents a previously unidentified MreB-binding site. Because RodZ 83 does lose rod shape, we propose that the helix-turn-helix interaction site may explain the rotation-independent morphogenesis roles of RodZ, whereas the juxta-membrane RodZ-MreB interaction site may enhance MreB rotation and explain the recent report that MreB is intimately membrane associated (21). The two MreB-binding sites may also partially functionally overlap as RodZ 83 does not fully phenocopy the ΔrodZ cell shape phenotype (SI Appendix, Fig.…”
Section: Rodz Mediates Mreb Rotation By Linking Cytoplasmic Mreb Tomentioning
confidence: 92%